Mesenchymal stem cell therapy on top of triple therapy with remdesivir, dexamethasone, and tocilizumab improves PaO2/FiO2 in severe COVID-19 pneumonia - Chen, Chih-Hao; Chang, Kuan-Cheng; Lin, Yen-Nien; Ho, Mao-Wang; Cheng, Meng-Yu; Shih, Wen-Hsin; Chou, Chia-Huei; Lin, Po-Chang; Chi, Chih-Yu; Lu, Min-Chi; Tien, Ni; Wu, Mei-Yao; et al. (Frontiers in Medicine, 2022)
Background: Despite patients with severe coronavirus disease (COVID-19) receiving standard triple therapy, including steroids, antiviral agents, and anticytokine therapy, health condition of certain patients continue to deteriorate. In Taiwan, the COVID-19 mortality has been high since the emergence of previous variants of this disease (such as alpha, beta, or delta). We aimed to evaluate whether adjunctive infusion of human umbilical cord mesenchymal stem cells (MSCs) (hUC-MSCs) on top of dexamethasone, remdesivir, and tocilizumab improves pulmonary oxygenation and suppresses inflammatory cytokines in patients with severe COVID-19. Methods: Hospitalized patients with severe or critical COVID-19 pneumonia under standard triple therapy were separated into adjuvant hUC-MSC and non-hUC-MSC groups to compare the changes in the arterial partial pressure of oxygen (PaO2)/fraction of inspired oxygen (FiO2) ratio and biological variables. Results: Four out of eight patients with severe or critical COVID-19 received either one (n = 2) or two (n = 2) doses of intravenous infusions of hUC-MSCs using a uniform cell dose of 1.0 × 108. Both high-sensitivity C-reactive protein (hs-CRP) level and monocyte distribution width (MDW) were significantly reduced, with a reduction in the levels of interleukin (IL)-6, IL-13, IL-12p70 and vascular endothelial growth factor following hUC-MSC transplantation. The PaO2/FiO2 ratio increased from 83.68 (64.34–126.75) to 227.50 (185.25–237.50) and then 349.56 (293.03–367.92) within 7 days after hUC-MSC infusion (P < 0.001), while the change of PaO2/FiO2 ratio was insignificant in non-hUC-MSC patients (admission day: 165.00 [102.50–237.61]; day 3: 100.00 [72.00–232.68]; day 7: 250.00 [71.00–251.43], P = 0.923). Conclusions: Transplantation of hUC-MSCs as adjunctive therapy improves pulmonary oxygenation in patients with severe or critical COVID-19. The beneficial effects of hUC-MSCs were presumably mediated by the mitigation of inflammatory cytokines, characterized by the reduction in both hs-CRP and MDW.